Risk assessment and information security ensuring of Starlink satellite communication channels at aviation enterprises - Bilonenko, V.Y.; Zarubinska, I.B.; Kostiuk, I.Y.; Kutinov, A.M. (Problems of Informatization and Management, 2025)
The article investigates the specific features of risk assessment and information security ensuring of Starlink satellite communication channels when integrated into aviation enterprises as critical infrastructure objects. A structural analysis of the Starlink architecture was conducted, and key threat vectors in the space, ground, and network segments were identified. Based on STRIDE and ISO/IEC 27005 methodologies, an adapted threat model for aviation enterprises was developed. A formalized approach to quantitative risk assessment considering segment architecture, asset criticality and security control effectiveness is proposed. Conceptual principles of a multi-layered protection system are substantiated, including network segmentation, additional cryptographic protection, multi-factor authentication and integration with security monitoring systems. The results can be applied during the integration of satellite communication channels into aviation enterprise information infrastructures.